Silica micropowder-boron nitride composite material as well as preparation method and application thereof
By using silicon micropowder-boron nitride composite materials in copper clad plates, the problems of insufficient insulation performance and poor thermal stability during high-frequency and high-speed signal transmission in traditional copper clad plates are solved, and the effects of improving insulation performance, reducing signal loss, enhancing thermal conductivity and mechanical strength are achieved.
Patent Information
- Application Number
- CN202510103430.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-22
AI Technical Summary
Traditional copper clad plates lack insulation performance during high-frequency and high-speed signal transmission, resulting in large signal transmission losses and poor thermal stability, which is prone to problems such as warping and stratification, which affects the long-term use of electronic equipment.
Using silicon micropowder-boron nitride composite material, the surface of the silicon micropowder is grafted by mixing silicon micropowder, silane coupling agent and organic solvent heating, and then reacts with a precursor solution of boron-containing compound and nitrogen-containing compound, and coats boron nitride on the surface of the silicon micropowder to prepare a silicon micropowder-boron nitride composite material with a specific structure.
It improves the insulation performance of copper clad plate, reduces signal transmission loss, meets the requirements of high-frequency and high-speed communication, and at the same time improves thermal conductivity, improves thermal stability, reduces thermal expansion coefficient, reduces warping and layering, and enhances mechanical strength and deformation resistance.
Smart Images

Figure CN119822376A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of material preparation, and in particular to a silicon micropowder-boron nitride composite material and a preparation method and application thereof. Background Art
[0002] Traditional copper-clad laminates have poor insulation performance when facing high-frequency and high-speed signal transmission, and are prone to large losses during signal transmission, affecting communication quality and data transmission speed. In addition, as the power of electronic devices increases, the heat generated increases, and traditional copper-clad laminates have insufficient thermal stability, and are prone to warping and delamination when the temperature changes, affecting the long-term use of electronic devices. Summary of the invention
[0003] In view of this, the present application provides a silicon micropowder-boron nitride composite material and a preparation method and application thereof to solve at least one of the above technical problems.
[0004] To achieve the above-mentioned objectives, in a first aspect, the present application provides a method for preparing a silicon micropowder-boron nitride composite material, which comprises: mixing silicon micropowder, a silane coupling agent and an organic solvent and heating them to graft amino groups on the surface of the silicon micropowder to obtain a seed liquid; mixing the seed liquid, an emulsifier and a solvent to obtain a seed emulsion; mixing a boron-containing compound, a nitrogen-containing compound and an organic solvent to obtain a precursor solution; mixing the seed emulsion and the precursor solution and heating them to coat boron nitride on the surface of the silicon micropowder, thereby obtaining a silicon micropowder-boron nitride composite material.
[0005] Based on the first aspect, in some possible implementations, the boron-containing compound includes one or more of boric acid, boron chloride and sodium borate tetradecahydrate, and the nitrogen-containing compound includes one or more of urea, melamine, hexamethylenetetramine, ethylenediamine and ammonia water.
[0006] Based on the first aspect, in some possible implementations, the pH of the precursor solution is 8 to 10.
[0007] Based on the first aspect, in some possible implementations, after heating the seed emulsion and the precursor solution, the preparation method further includes: washing, drying and annealing the heated product.
[0008] Based on the first aspect, in some possible implementations, the emulsifier includes one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate and hexadecyltrimethylammonium bromide.
[0009] Based on the first aspect, in some possible implementations, the mass ratio of the silane coupling agent to the silicon powder is 2% to 10%.
[0010] Based on the first aspect, in some possible implementations, the mass ratio of the emulsifier to the silicon micropowder is 0.5% to 2.5%.
[0011] Based on the first aspect, in some possible implementations, the mass ratio of the boron-containing compound to the nitrogen-containing compound is 40% to 60%.
[0012] Based on the first aspect, in some possible implementations, the mass ratio of the boron-containing compound to the silicon micropowder is 12.5% to 37.4%.
[0013] Based on the first aspect, in some possible implementations, the temperature after heating is 90° C. to 140° C.
[0014] In a second aspect, the present application provides a silicon micropowder-boron nitride composite material prepared by the above-mentioned preparation method, wherein the silicon micropowder-boron nitride composite material comprises a core and a coating disposed on at least a portion of the surface of the core, wherein the core comprises silicon micropowder and the coating comprises boron nitride.
[0015] Based on the second aspect, in some possible implementations, the mass ratio of boron nitride to silicon powder is 5% to 15%.
[0016] Based on the second aspect, in some possible implementations, the boron nitride includes hexagonal boron nitride.
[0017] In a third aspect, the present application provides a copper clad laminate comprising a copper foil layer and a dielectric layer stacked together, wherein the dielectric layer comprises the above-mentioned silicon micropowder-boron nitride composite material.
[0018] The preparation method of the present application compounds silicon micropowder with boron nitride to obtain a silicon micropowder-boron nitride composite material with a specific structure, which combines the advantages of low thermal expansion coefficient, insulation of silicon micropowder and high thermal conductivity, low dielectric constant of boron nitride, and can more fully realize the complementary optimization of the performance of the two materials; wherein, grafting amino groups on the surface of silicon micropowder is conducive to enhancing the binding force between the core silicon micropowder and the coating boron nitride, so that the structure of the obtained silicon micropowder-boron nitride composite material is more stable. The obtained silicon micropowder-boron nitride composite material is applied to copper clad laminates, which is conducive to improving the insulation performance of copper clad laminates, reducing signal transmission loss, and meeting high-frequency and high-speed communication requirements. At the same time, it is also conducive to improving thermal conductivity, better improving thermal stability, reducing thermal expansion coefficient, reducing warping and delamination, and can also enhance the mechanical strength of copper clad laminates and improve their anti-deformation ability. In addition, the obtained silicon micropowder-boron nitride composite material has good binding properties with the resin matrix of copper clad laminates, which is conducive to improving the compatibility of the interface between the copper clad laminate filler and the resin matrix, thereby helping to better improve the comprehensive performance of the copper clad laminates. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1A schematic flow chart of a method for preparing a silicon micropowder-boron nitride composite material provided in one embodiment of the present application. DETAILED DESCRIPTION
[0020] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0021] In order to improve the existing problems of copper clad laminates, filling copper clad laminates with high-performance ceramic materials has become an important research direction. Silicon micropowder is widely used in copper clad laminate filling materials due to its good insulation, low thermal expansion coefficient and low cost. However, single silicon micropowder still needs to be improved in improving the thermal conductivity and mechanical properties of copper clad laminates. Boron nitride has excellent properties such as high thermal conductivity, good chemical stability and low dielectric constant. In theory, the combination of boron nitride and silicon micropowder is expected to complement each other's advantages, thereby achieving the purpose of improving the comprehensive performance of copper clad laminates.
[0022] However, the inventors of the present application have found that there are many problems in the preparation of silicon micropowder and boron nitride composite materials for copper-clad laminates using existing methods. For example, the existing preparation process lacks control over the structure and composition ratio of the composite material, resulting in large fluctuations in product performance and poor consistency. Moreover, the preparation process is complicated and costly, which is not conducive to large-scale industrial production. In addition, the composite material prepared by the existing method has poor interface compatibility when combined with the resin matrix of the copper-clad laminate, and cannot fully exert its reinforcing effect.
[0023] Based on this, one embodiment of the present application provides a method for preparing a silicon micropowder-boron nitride composite material, please refer to Figure 1 , the preparation method comprises: Step 1: Mix silicon micropowder, silane coupling agent and organic solvent and heat them to graft amino groups on the surface of silicon micropowder to obtain seed solution.
[0024] The amino groups grafted onto the surface of silicon micropowder are beneficial to improving the interface affinity of silicon micropowder and enhancing the subsequent bonding force between silicon micropowder and coating.
[0025] In some embodiments, the temperature after heating is 90°C to 140°C. For example, the temperature after heating can be 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, or any value within the range formed by any two of the above values. Controlling the temperature within the above range is conducive to the grafting of amino groups on the surface of the silicon powder.
[0026] In some embodiments, the mass ratio of the silane coupling agent to the silicon micropowder is 2% to 10%. For example, the mass ratio of the silane coupling agent to the silicon micropowder can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any value within the range formed by any two of the above values. Controlling the ratio of silicon micropowder and silane coupling agent within the above range is conducive to fully grafting amino groups on the surface of silicon micropowder, improving the subsequent bonding force with the coating, and thus helping to improve the performance of the silicon micropowder-boron nitride composite material.
[0027] Step 2: Mix the seed liquid, emulsifier and solvent to obtain seed emulsion.
[0028] Converting the above seed liquid into an emulsion system is beneficial to improving the dispersibility of the seed liquid components, thereby facilitating the subsequent smooth reaction with the coating material.
[0029] In some embodiments, the emulsifier includes one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate and hexadecyl trimethyl ammonium bromide. The above emulsifier can be selected to convert the seed liquid into an emulsion system, which is conducive to a better subsequent reaction with the coating and promotes the formation of the silicon micropowder-boron nitride composite material of the present application.
[0030] In some embodiments, the mass ratio of the emulsifier to the silicon micropowder is 0.5% to 2.5%. For example, the mass ratio of the emulsifier to the silicon micropowder can be 0.5%, 1%, 1.5%, 2%, 2.5%, or any value within the range formed by any two of the above values. Controlling the mass ratio of the emulsifier to the silicon micropowder is conducive to improving the consistency of the composition of the obtained silicon micropowder-boron nitride composite material, making the performance of the obtained silicon micropowder-boron nitride composite material more controllable, and is conducive to better improving the improvement of the comprehensive performance of the copper clad laminate.
[0031] Step 3: Mix the boron-containing compound, the nitrogen-containing compound and the organic solvent to obtain a precursor solution.
[0032] In some embodiments, the boron-containing compound includes one or more of boric acid, boron chloride, and sodium borate tetradecahydrate, and the nitrogen-containing compound includes one or more of urea, melamine, hexamethylenetetramine, ethylenediamine, and ammonia water.
[0033] In some embodiments, the mass ratio of the boron-containing compound to the nitrogen-containing compound is 40% to 60%. For example, the mass ratio of the boron-containing compound to the nitrogen-containing compound can be 40%, 43%, 45%, 48%, 50%, 52%, 55%, 57%, 60%, or any value within the range of any two of the above values. It is beneficial to control the content of reactive substances in the precursor solution and to promote the formation of the silicon micropowder-boron nitride composite material of the present application.
[0034] In some embodiments, the mass ratio of the boron-containing compound to the silicon micropowder is 12.5% to 37.4%. For example, the mass ratio of the boron-containing compound to the silicon micropowder can be 12.5%, 14.5%, 17.5%, 20.5%, 23.5%, 26.5%, 29.5%, 32.5%, 35.5%, 37.4%, or any value within the range of any two of the above values. It is beneficial to control the content of boron nitride coated on the surface of the silicon micropowder, and the appropriate amount of boron nitride coating is beneficial to better combine the performance advantages of silicon micropowder and boron nitride, thereby improving the performance of the silicon micropowder-boron nitride composite material.
[0035] In some embodiments, the pH of the precursor solution is 8 to 10. The precursor solution with a preset pH has good reactivity, and promotes the reaction with the seed emulsion components under subsequent heating, thereby promoting the formation of the silicon powder-boron nitride composite material of the present application.
[0036] Step 4: Mix the seed emulsion and the precursor solution and heat them to coat the surface of the silicon micropowder with boron nitride, thereby obtaining a silicon micropowder-boron nitride composite material.
[0037] In some embodiments, the temperature after heating is 90° C. to 140° C. For example, the temperature after heating can be 90° C., 100° C., 110° C., 120° C., 130° C., 140° C., or any value within the range formed by any two of the above values. Within the above temperature range, it is beneficial for the precursor solution to form a boron nitride coating on the surface of the silicon powder.
[0038] In some embodiments, after heating the seed emulsion and the precursor solution, the preparation method further comprises: washing, drying and annealing the heated product. Washing is used to remove unreacted substances, drying is used to remove washing liquid, and annealing is beneficial to reducing the internal stress of the silicon micropowder-boron nitride composite material, optimizing the structure of the silicon micropowder-boron nitride composite material, and improving the stability of the silicon micropowder-boron nitride composite material.
[0039] The preparation method of the present application compounds silicon micropowder with boron nitride to obtain a silicon micropowder-boron nitride composite material with a specific structure, which combines the advantages of low thermal expansion coefficient, insulation of silicon micropowder and high thermal conductivity, low dielectric constant of boron nitride, and can more fully realize the complementary optimization of the performance of the two materials; wherein, grafting amino groups on the surface of silicon micropowder is conducive to enhancing the binding force between the core silicon micropowder and the coating boron nitride, so that the structure of the obtained silicon micropowder-boron nitride composite material is more stable. The obtained silicon micropowder-boron nitride composite material is applied to copper clad laminates, which is conducive to improving the insulation performance of copper clad laminates, reducing signal transmission loss, and meeting high-frequency and high-speed communication requirements. At the same time, it is also conducive to improving thermal conductivity, better improving thermal stability, reducing thermal expansion coefficient, reducing warping and delamination, and can also enhance the mechanical strength of copper clad laminates and improve their anti-deformation ability. In addition, the obtained silicon micropowder-boron nitride composite material has good binding properties with the resin matrix of copper clad laminates, which is conducive to improving the compatibility of the interface between the copper clad laminate filler and the resin matrix, thereby helping to better improve the comprehensive performance of the copper clad laminates.
[0040] Therefore, the preparation method of the present application realizes the regulation of the structure and performance of the silicon micropowder-boron nitride composite material, which is conducive to improving the consistency of the prepared silicon micropowder-boron nitride composite material. In addition, the preparation method of the present application has a relatively simple operation process, controllable cost, good industrial production prospects, and is expected to bring economic benefits and technological innovation to the copper clad laminate industry.
[0041] One embodiment of the present application also provides a silicon micropowder-boron nitride composite material, which is prepared by the above-mentioned preparation method. The silicon micropowder-boron nitride composite material includes a core and a coating provided on at least a portion of the surface of the core, wherein the core includes silicon micropowder and the coating includes boron nitride.
[0042] In the silicon micropowder-boron nitride composite material of the present application, silicon micropowder and boron nitride form a specific structural relationship, which is conducive to better combining the insulation of silicon micropowder and the high thermal conductivity and low dielectric constant of boron nitride. Silicon micropowder and boron nitride can more fully realize the complementary optimization of the performance of the two materials through the preset structural relationship. Among them, the amino group on the surface of silicon micropowder is conducive to enhancing the binding force between the core silicon micropowder and the coating boron nitride, making the structure of the silicon micropowder-boron nitride composite material more stable. Applied in copper clad laminates, it is conducive to improving the insulation performance of copper clad laminates, reducing signal transmission loss, and meeting high-frequency and high-speed communication requirements. At the same time, it is also conducive to improving thermal conductivity, better improving thermal stability, reducing thermal expansion coefficient, reducing warping and delamination, and can also enhance the mechanical strength of copper clad laminates and improve their anti-deformation ability. In addition, the silicon micropowder-boron nitride composite material of the present application has good binding properties with the resin matrix of the copper clad laminate, which is conducive to improving the compatibility of the interface between the copper clad laminate filler and the resin matrix, thereby helping to better improve the comprehensive performance of the copper clad laminate.
[0043] In some embodiments, the mass ratio of boron nitride to silicon powder is 5% to 15%. For example, the mass ratio of boron nitride to silicon powder can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, or any value within the range of any two of the above values. Controlling the mass ratio of boron nitride to silicon powder within the above range is conducive to better exerting the advantages of silicon powder and boron nitride, and more fully realizing the complementary optimization of the performance of the two materials, thereby helping to improve the performance of the silicon powder-boron nitride composite material.
[0044] In some embodiments, the boron nitride includes hexagonal boron nitride. The coating of the silicon powder-boron nitride composite material can be selected from the above-mentioned types of boron nitride, which can achieve the effect of complementary optimization of material properties, and the coating is conducive to improving the thermal conductivity and thermal stability of the copper clad laminate.
[0045] An embodiment of the present application further provides a copper-clad laminate, comprising a copper foil layer and a dielectric layer stacked together, wherein the dielectric layer comprises the above-mentioned silicon micropowder-boron nitride composite material.
[0046] The silicon micropowder-boron nitride composite material of the present application has good bonding with the copper clad laminate resin, which is beneficial to improving the compatibility of the interface between the copper clad laminate filler and the resin matrix. Therefore, the copper clad laminate whose dielectric layer includes the silicon micropowder-boron nitride composite material has improved comprehensive performance.
[0047] The scheme of the present application will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present application and cannot be construed as limiting the present application. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.
[0048] Embodiment 1: (1) A silicon micropowder-boron nitride composite material, the preparation method of which comprises: Step 1: Weigh a certain mass of spherical silicon powder and pour it into ethanol, turn on the stirring device to evenly disperse the silicon powder in the ethanol; then, weigh a corresponding mass of γ-aminopropyltriethoxysilane according to 2%~10% of the mass of the silicon powder and slowly add it to the above dispersion system, put the round-bottom flask into an oil bath at 120°C, and stir the reaction for 4 hours; after the reaction is completed, a seed solution is obtained.
[0049] Step 2: According to 0.5%~2.5% of the mass of silicon micropowder, weigh the corresponding mass of sodium dodecyl sulfate, add it into water, and stir to make it completely dissolved; add the seed liquid into the aqueous solution containing sodium dodecyl sulfate, and ultrasonicate for 30 minutes to evenly disperse the seed liquid in the aqueous solution to form a stable emulsion system to obtain the seed emulsion.
[0050] Step 3: Weigh a certain mass of urea, and weigh a corresponding mass of boric acid according to 40%~60% of the mass of urea. First, add the boric acid to ethanol and stir to dissolve it. Similarly, add urea to another ethanol, stir to dissolve, mix the two solutions of boric acid and urea evenly, and then use ammonia water to adjust the pH to between 8 and 10, stop adding ammonia water, stir and react for 2 hours to obtain a precursor solution.
[0051] Step 4: Slowly add the precursor solution to the reaction vessel containing the seed emulsion through a constant pressure dropping funnel, and keep stirring during the dropping process; after the dropping is completed, place the reaction vessel in an oil bath, heat it to 120 °C, and continue stirring for 8 h.
[0052] Step 5: After the reaction is completed, the product of the above reaction is washed by multiple centrifugation and then vacuum dried at 70 °C; the dried product is placed in a muffle furnace, heated to 900 °C at a heating rate of 5 °C / min, and annealed at this temperature for 3 h; after the annealing is completed, the temperature is lowered to room temperature at 5 °C / min to obtain a silicon micropowder-boron nitride composite material.
[0053] (2) A copper clad laminate, the preparation method of which comprises: The first step: fully mixing the synthesized silicon micropowder-boron nitride composite material with the PTFE emulsion to obtain co-coagulation powder.
[0054] Step 2: The co-coagulated powder is subjected to aging, extrusion and calendaring to obtain a raw base film (i.e., a dielectric layer).
[0055] Step 3: Copper foils are coated on both sides of the raw base film and vacuum pressed at high temperature to obtain a copper clad laminate.
[0056] Embodiment 2: (1) A silicon micropowder-boron nitride composite material, the preparation method of which is different from that of Example 1 in that, in the third step, urea is replaced by melamine, and a corresponding mass of boric acid is weighed according to 40% to 60% of the mass of melamine. The remaining steps are basically the same as those of Example 1.
[0057] (2) A copper clad laminate, the preparation method of which is substantially the same as that of Example 1.
[0058] Comparative Example 1: A conventional copper clad laminate, the preparation method of which comprises: The first step is to adjust the glue: add bisphenol A epoxy resin into the reactor, heat it to 50 ℃ to 70 ℃, stir it to make it completely dissolved, add curing agent, initiator, and flame retardant in turn, and continue stirring for 30 minutes to 60 minutes. The speed is controlled at 50 r / min to 300 r / min to ensure that the additives are evenly dispersed to form a uniform and stable epoxy resin glue solution, among which the curing agent accounts for 5% to 15% of the epoxy resin mass percentage, the accelerator accounts for 0.5% to 3%, and the flame retardant accounts for 10% to 30%.
[0059] The second step is to dip the glass fiber cloth into the epoxy resin solution, and control the dipping speed from 0.5 m / min to 2 m / min to ensure sufficient dipping.
[0060] The third step is scraping glue and drying: Use a scraper or squeeze roller to remove excess glue on the surface of the glass fiber cloth to control the resin content of the prepreg to 40% to 60%. Then send it to the drying furnace and dry it at 120℃ to 150℃ for 10 minutes to 30 minutes to fully evaporate the solvent to obtain a prepreg. Step 4: Lamination: Laminating the copper foils on both sides of the prepreg obtained above by high temperature vacuum lamination to obtain a copper clad laminate.
[0061] Comparative Example 2: (1) A silicon micropowder-boron nitride composite material, the preparation method of which is different from that of Example 1 in that: spherical silicon micropowder and hexagonal boron nitride powder with a mass ratio of 10:1 are weighed and fully mixed by mechanical stirring to obtain a silicon micropowder-boron nitride composite material.
[0062] (2) A copper clad laminate, the preparation method of which is substantially the same as that of Example 1.
[0063] Comparative Example 3: (1) A silicon micropowder-boron nitride composite material, the preparation method of which is different from that of Example 1 in that: in the first step, the silane coupling agent is removed and the silicon micropowder is not surface modified; that is, the first step is: weigh a certain mass of spherical silicon micropowder and pour it into ethanol, turn on the stirring device to evenly disperse the silicon micropowder in the ethanol, transfer it into an oil bath pot at 120°C, and stir and react for 4 hours. The remaining steps are basically the same as those of Example 1.
[0064] (2) A copper clad laminate, the preparation method of which is substantially the same as that of Example 1.
[0065] The present application also conducted the following performance tests on the copper clad laminates of Examples 1-2 and Comparative Examples 1-3: (1) Dielectric constant and dielectric loss factor test: The dielectric properties are tested using the Split Cylindrical Resonator (SPDR) method (a standard of the American Society for Testing and Materials, method number ASTM2520). First, connect the 10 GHz test fixture to the network analyzer and measure the center frequency f of the cavity. c And the quality factor Q c Then, insert the sample and measure the center frequency f again after loading the sample. s And the loaded quality factor Q s . Then through the following formula: Dielectric constant (Dk) = , ; Dielectric loss (Df) = ; Calculate the dielectric constant and dielectric loss, where f c is the center frequency of the cavity, f s is the center frequency of the sample, Q c is the cavity quality factor, Q s is the sample quality factor, V c is the volume of the cavity, V s is the volume of the sample.
[0066] (2) Thermal expansion coefficient test: Thermomechanical analysis method, IPC TM 650 2.4.24.4 (-55~288℃), the thermal mechanical analyzer heats the sample and calculates the thermal expansion coefficient α by measuring the length change of the sample at different temperatures i : Among them, α i is the thermal expansion coefficient of the material in the i direction (i=X,Y,Z), in ppm / ℃, ΔL i It is the change in length of the material in the i direction (i=X,Y,Z), in μm, L 0i is the initial length of the material in the i direction (i=X,Y,Z), in meters, and ΔT is the change in temperature, in degrees Celsius.
[0067] (3) Thermal conductivity test: Using the steady-state heat flow method, a certain heat flow (heat flow output is detected by a heat flow sensor) and pressure are applied to the sample above and below the sample. The thickness of the sample and the temperature difference between the hot plate and the cold plate are tested to obtain the thermal conductivity λ of the sample: Where λ is the thermal conductivity of the sample in W / Mk, Q h is the heat flux output of the upper sensor in W / m 2 , Q cis the heat flux output of the lower sensor in W / m 2 , L is the thickness of the sample, in m, and ΔT is the temperature difference between the upper and lower surfaces of the sample, in K.
[0068] (4) Peel strength test: ① Sample preparation: Cut a sample with a length of 120 mm and a width of 70 mm from the area 2.54 mm above the edge of the laminated copper clad board, stick an anti-corrosion tape on the sample, and use ferric chloride etching solution to make three test strips with a width of 3.18 mm and a length of 100 mm in the sample area.
[0069] ② Sample measurement: Use a universal testing machine, with the copper foil side of the test strip facing up, align the test strip with the center of the sample holder, place the pinhole plate on the test strip, place the clamping head in the hole, align the copper foil strip with the inclined slot, clamp the copper foil strip with the sample clamp, make the peeling direction 90 degrees to the insulating substrate, and start peeling at a rate of 50.8 mm / min.
[0070] ③ Calculate the peel strength: Peel strength = minimum peel force / sample width.
[0071] Please refer to Table 1 for the above test results.
[0072] Table 1. Performance test results of copper clad laminates of Examples 1-2 and Comparative Examples 1-3 of the present application The silicon micropowder-boron nitride composite material obtained by the preset preparation method in Examples 1-2 of the present application includes a core (mainly silicon micropowder) and a coating (mainly boron nitride) on the surface of the core, and an amino group is also provided on the surface of the silicon micropowder to enhance the bonding force between the silicon micropowder and the boron nitride, and has a core-shell structure. The silicon micropowder-boron nitride composite material can better combine the advantages of the low thermal expansion coefficient and insulation of silicon micropowder with the high thermal conductivity and low dielectric constant of boron nitride. The silicon micropowder and boron nitride can better achieve the complementary optimization of the performance of the two materials by compounding through a preset structural relationship. Therefore, the copper clad laminate obtained in Examples 1-2 of the present application has improved insulation, low signal transmission loss, meets the requirements of high-frequency and high-speed communication, and at the same time, has improved thermal conductivity, good thermal stability, is conducive to reducing warping and delamination, and the comprehensive performance of the copper clad laminate is improved.
[0073] Compared with Example 1, Comparative Example 1 is a traditional copper clad laminate, and its performance is obviously inferior to that of Example 1 of the present application, which shows that the application of the silicon micropowder-boron nitride composite material of the present application to the copper clad laminate can significantly improve the comprehensive performance of the copper clad laminate.
[0074] Compared with Example 1, the composite material of Comparative Example 2 is simply mixed with silicon micropowder and boron nitride, and the silicon micropowder-boron nitride composite material of the present application cannot be obtained. The performance of the obtained copper clad laminate is not as good as that of Example 1 of the present application, which shows that in the silicon micropowder-boron nitride composite material obtained by the preparation method of the present application, the silicon micropowder and boron nitride are combined through a preset structural relationship to better achieve the complementary optimization of the performance of the two materials.
[0075] Compared with Example 1, the composite material of Comparative Example 3 did not use a silane coupling agent to modify the surface of the silicon micropowder, and the performance of the obtained composite material was not as good as that of the embodiment. This shows that the present application uses a silane coupling agent to graft amino groups on the surface of the silicon micropowder, which is beneficial to better improve the performance of the obtained silicon micropowder-boron nitride composite material.
[0076] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.
Claims
1. A method for preparing a silicon micropowder-boron nitride composite material, characterized in that: The preparation method comprises: Mixing silicon micropowder, a silane coupling agent and an organic solvent and heating the mixture to graft amino groups on the surface of the silicon micropowder to obtain a seed solution; mixing the seed liquid, emulsifier and solvent to obtain a seed emulsion; mixing a boron-containing compound, a nitrogen-containing compound and an organic solvent to obtain a precursor solution; The seed emulsion and the precursor solution are mixed and heated to coat the surface of the silicon micropowder with boron nitride, thereby obtaining the silicon micropowder-boron nitride composite material.
2. The preparation method according to claim 1, characterized in that The boron-containing compound includes one or more of boric acid, boron chloride and sodium borate tetradecahydrate, and the nitrogen-containing compound includes one or more of urea, melamine, hexamethylenetetramine, ethylenediamine and ammonia water.
3. The preparation method according to claim 1, characterized in that: The pH of the precursor solution is 8 to 10.
4. The preparation method according to claim 1, characterized in that: After heating the seed emulsion and the precursor solution, the preparation method further comprises: washing, drying and annealing the heated product.
5. The preparation method according to claim 1, characterized in that: The emulsifier includes one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate and hexadecyltrimethylammonium bromide.
6. The preparation method according to claim 1, characterized in that: The preparation method satisfies at least one of the following conditions: (1) The mass ratio of the silane coupling agent to the silicon powder is 2% to 10%; (2) The mass ratio of the emulsifier to the silicon powder is 0.5% to 2.5%; (3) The mass ratio of the boron-containing compound to the nitrogen-containing compound is 40% to 60%; (4) The mass ratio of the boron-containing compound to the silicon micropowder is 12.5% to 37.4%.
7. The preparation method according to claim 1, characterized in that The temperature after heating is 90°C to 140°C.
8. A silicon micropowder-boron nitride composite material, characterized in that: The silicon micropowder-boron nitride composite material is prepared by the preparation method according to any one of claims 1 to 7, comprising a core and a coating provided on at least a portion of the surface of the core, the core comprising silicon micropowder, and the coating comprising boron nitride.
9. The silicon micropowder-boron nitride composite material according to claim 8, characterized in that: The silicon powder-boron nitride composite material satisfies at least one of the following conditions: (1) The mass ratio of the boron nitride to the silicon powder is 5% to 15%; (2) The boron nitride includes hexagonal boron nitride.
10. A copper-clad laminate, comprising a copper foil layer and a dielectric layer stacked together, characterized in that: The dielectric layer comprises the silicon micropowder-boron nitride composite material as described in claim 8 or 9.
Citation Information
Patent Citations
Preparation method of boron nitride composite material
CN103910345A
Modified hexagonalboron nitride powder and preparation method and application thereof
CN109337409A
High-thermal-conductivity radiation refrigeration coating material and preparation method thereof
CN119192916A